Gender Norms Matter in Aquatic Agricultural Innovation Process: Empirical Insights from Bangladesh - Behailu, Lemlem (WorldFish, 2017)
Presented by Lemlem Behailu (World Fish), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.